Significance of Providing Index-based Accurate Treatment Time Estimates to Patients Before Orthodontic Treatment - Samreen, Shama; Joneja, Purva (Orthodontic Journal of Nepal, 2022)
Introduction: Orthodontic treatment duration has always been a topic of concern to patients and one of the aims of orthodontic treatment is to minimize the overall treatment time. Aim and Objective: To determine the benefits of providing index-based accurate treatment duration to patients before orthodontic treatment in practice management. Materials and Method: A cross-sectional questionnaire survey was the chosen method of research. A multiple choice and dichotomous question questionnaire was structured with 15 relevant questions to be filled in by the respondents to deduce the required information. The survey was circulated to 100 postgraduate students and orthodontists using various social media platforms who responded to the survey. Result: In general, young adults (51.0%) demanded the approximate treatment time before treatment and 50% of the clinicians provided an accurate estimate of treatment time to the patients before treatment. For simple orthodontic cases, PAR Score was the index of choice and for complex orthodontic cases, ABO-DI index was preferred. Conclusion: Accurate estimation of treatment duration before treatment resulted in highly motivated, happy and satisfied patients. It also saved the time and resources of orthodontists.